In vitro Antioxidative and Cytotoxicity Effects of Justicia gangetica Leaves and Their Application in Cooked Chicken Patties - Nitteranon, Viriya; Fackthongkum, Pawinee; Pooratanachareonchai, Tanyarat (Journal of Applied Research on Science and Technology (JARST), 2017)
Justicia gangetica is the edible folk vegetable found in tropical area including Thailand. The study was conducted to investigate total phenolic contents, antioxidative and cytotoxic activities of crude extract of J. gangetica leaves (JGL) and determined its potential as natural food preservative in chicken patties. The ethanol extract of JGL contained highest total phenolic contents and DPPH-radical scavenging activity (P ≤ 0.05) compared to JGL water extract. Cell toxicity was evaluated in HT-29, MCF-7 and Vero cells with different concentrations of JGL ethanol extracts using MTT assay. The result showed no cytotoxic effect of JGL extracts at 125-500 µg/ml. Thiobarbituronic acid-reactive substance (TBARS) value was determined during refrigerated storage. The lower TBARS levels were noticed in chicken patties containing JGL and BHT, comparing to control (P ≤ 0.05). These results indicate that JGL can be used as food preservative in meat product to effectively lower lipid oxidation.